Pelatihan Pembuatan E- LKPD Bagi Guru dalam Pemanfaatan Media Pembelajaran Digital Berbasis Stem Menggunakan Canva di MI Al Istiqlal Karawang - Nurina Kurniasari Rahmawati; Fitriyani Fitriyani; Abdul Hakim Ma’ruf (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Digital transformation in education requires teachers to develop the competence to integrate technology and innovative learning approaches into classroom practices. However, a needs analysis at MI Al Istiqlal Karawang revealed that 54% of teachers experienced difficulties in using digital learning media, 56% predominantly relied on conventional teaching methods, and 50% of the available learning media did not optimally support the learning process. This community service program aimed to enhance teachers’ competence in understanding Science, Technology, Engineering, and Mathematics(STEM)-based learning, utilizing Canva, and developing interactive and contextual STEM-based Electronic Student Worksheets (E-LKPD). The program was implemented through needs analysis, socialization, hands-on training, E-LKPD development practice, mentoring, and evaluation. A total of 50 teachers from MI Al Istiqlal Karawang participated in the program. Evaluation was conducted through observation, product assessment, participant responses, and pre-test and post-test measures, with paired analysis conducted for 12 teachers with complete datasets. The results demonstrated an increase in the mean competency score from 22.33 in the pre-test to 28.42 in the post-test, representing an improvement of 6.08 points (27.2%). The paired sample t-test indicated a statistically significant difference between the pre-training and post-training scores (t = 3.562; df = 11; p = 0.004 < 0.05). Improvements were also observed in teachers’ understanding of STEM-based digital learning media, Canva proficiency, E-LKPD development skills, and readiness to implement the developed media in classroom instruction. Furthermore, participants successfully produced STEM-based E-LKPDs for Mathematics, Science, and Pancasila Education. These findings indicate that practice-oriented training combined with mentoring is effective in strengthening teachers’ digital and professional competencies and supporting the transformation toward innovative, interactive, and 21st-century learning.